Pendidikan Kepemimpinan Berbasis Psikologi Sosial dalam Komunikasi Publik untuk Mitigasi Konflik dan Diplomasi Kemanusiaan pada Situasi Darurat Kebencanaan - Barep Prasetyo, Zanuar; Aditya Novaldi, Rifki; Arif Afandi, Rizky; Poniman, Poniman (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2025)
This study examines how social psychology–based leadership education enhances public communication skills among leaders during disaster emergencies and contributes to social conflict mitigation. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and focus group discussions involving local disaster management officials, community leaders, humanitarian volunteers, educators, and social psychologists. The findings reveal that integrating social psychology principles into leadership education strengthens leaders’ ability to understand group dynamics, manage public emotions, and deliver empathetic and credible messages. Empathy-driven and socially aware leadership communication proved effective in reducing social tensions and fostering community trust and collaboration during crises. This research contributes to the theoretical development of transformational leadership in disaster contexts and offers practical implications for leadership training institutions and disaster management organizations to design psychosocially grounded leadership education that supports humanitarian coordination and resilience.